Poly(Lactic Acid) 2010
DOI: 10.1002/9780470649848.ch10
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of Poly(Lactic Acid)

Abstract: The readers of this chapter are expected to come from a wide variety of backgrounds with varying degrees of expertise in polymer materials science. Accordingly, a detailed understanding of the rheological properties of polymers is, for many readers, an unknown subject. With these factors in mind, the first topic to be addressed is, What is rheology and why is it important?Simply stated, rheology is the study of the flow and deformation of matter. Rheology is a subfield of continuum mechanics that combines elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 43 publications
2
29
0
Order By: Relevance
“…G N 0 values estimated from the curves are as follows: 3.97 × 10 5 Pa for mixture PLA and 2.42 × 10 5 Pa for natural PLA. These results are in good agreement with previous values reported by Dorgan (5 × 10 5 Pa), Cooper‐White et al . (5.5 × 10 5 Pa), and Grijpma et al .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…G N 0 values estimated from the curves are as follows: 3.97 × 10 5 Pa for mixture PLA and 2.42 × 10 5 Pa for natural PLA. These results are in good agreement with previous values reported by Dorgan (5 × 10 5 Pa), Cooper‐White et al . (5.5 × 10 5 Pa), and Grijpma et al .…”
Section: Resultssupporting
confidence: 93%
“…Tuminello et al . showed that MWD can be determined from linear viscoelastic melt properties, such as the shear storage modulus, G ′( ω ), or the stress relaxation modulus G ( t ), and from viscosity versus shear rate curves …”
Section: Introductionmentioning
confidence: 99%
“…The flow rate was 1 mL · min −1 , runtime was 40 min, and temperature was 35 °C. The Mark‐Houwink constants K = 0.0131 (mL · g −1 ) and a = 0.759 for chloroform at 30 °C for dilute PLLA solution were used 33…”
Section: Methodsmentioning
confidence: 99%
“…To disregard the thermal history during processing or storage, the second heating cycle was used to determine the glass transition temperature ( T g ), cold crystallization onset ( T co ), melting temperature ( T m ), and to calculate the enthalpy of cold crystallization ( ΔH c ) and fusion ( ΔH m ). The percent crystallinity X c (%) was estimated using the following equation: Xctrue(%true)=ΔHmΔHcΔHmctrue(1xtrue)×100 where Δ H m is enthalpy of fusion; Δ H c is the enthalpy of cold crystallization; Δ Hmc is enthalpy of fusion of pure crystalline PLA (Δ Hmc = 93.1 J/g) and x represents the mass fraction of the MOF in the films. Universal Analysis software version 2000 (TA Instruments, DE) was used to analyze the data.…”
Section: Methodsmentioning
confidence: 99%